1989
DOI: 10.1016/0378-1097(89)90350-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a protease of Streptococcus sanguis G9B which degrades the major salivary adhesin

Abstract: An endogenous enzyme present in cell surface extracts of Streptococcus sanguis strain G9B degraded the major salivary adhesin of the organism. The enzyme showed optimal activity between 50 and 65 degrees C and was inactivated at higher temperatures. The activity at these unusually high temperatures seemed to be a consequence of release from the cell surface since intact whole G9B cells showed greater activity at 37 degrees C. The enzyme was not found in culture supernatants of G9B cells. The pH range for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The specimens were finally examined in an electron microscope (Philips CM 12) at an accelerating voltage of 80 kV Extraction of S. sanguis OMZ 9 ceii surface proteins Bacteria were harvested from a 2-liter batch culture in FUM, by centrifuging at 10,000 x^^ for 10 min at 4"C. They were washed three times with distilled water (48,000 xg, 15 min, 4 C) and subjected to the barbital extraction procedure described by Lamont et al (30) with the following modifications. The pellet was suspended in 550 ml of cold 2 mM sodium 5,5-diethylbarbiturate buffer (pH 8.6) supplemented with 1 mM iodoacetic acid, to inhibit endogenous protease activities (28). After shaking for 30 min at 4°C, the suspension was centrifuged (48,000 x^, 15 min, 4"C), and the supernatant collected.…”
Section: Binding Of Colioidal Goid-labeiied Cgp To Oral Bacteriamentioning
confidence: 99%
“…The specimens were finally examined in an electron microscope (Philips CM 12) at an accelerating voltage of 80 kV Extraction of S. sanguis OMZ 9 ceii surface proteins Bacteria were harvested from a 2-liter batch culture in FUM, by centrifuging at 10,000 x^^ for 10 min at 4"C. They were washed three times with distilled water (48,000 xg, 15 min, 4 C) and subjected to the barbital extraction procedure described by Lamont et al (30) with the following modifications. The pellet was suspended in 550 ml of cold 2 mM sodium 5,5-diethylbarbiturate buffer (pH 8.6) supplemented with 1 mM iodoacetic acid, to inhibit endogenous protease activities (28). After shaking for 30 min at 4°C, the suspension was centrifuged (48,000 x^, 15 min, 4"C), and the supernatant collected.…”
Section: Binding Of Colioidal Goid-labeiied Cgp To Oral Bacteriamentioning
confidence: 99%
“…Their metabolic activities will modify the newly colonized habitat and influence subsequent events during ecologic succession. Previous investigators have demonstrated that protease activity from S. sanguis can modify human salivary molecules (12). Immunofluorescence studies demonstrate that the 146-kDa protease is detectable on the bacterial cell surface and may therefore modify salivary molecules on the tooth surface.…”
Section: Discussionmentioning
confidence: 98%
“…Although studies describe and characterize specific immunoglobulin A (IgA) proteases from these early colonizers (1,16), less is known regarding specific molecules mediating the general proteolytic activities elaborated by these organisms. S. oralis and related streptococci are known to produce protease and peptidase activities (2,4,12,18,19). These investigations have focused on the physiological role of these activities, in particular, their probable role in meeting the amino nitrogenous demands of the organism's metabohsm.…”
mentioning
confidence: 99%
“…A more plausible explanation is that the lower molecular mass molecules were generated by proteolytic activity. Oral streptococci produce a number of proteases that can be released from the cells and may degrade surface proteins (Cowman & Baron, 1991 ;Floders et al, 1987 ;Lamont & Rosan, 1989;Rodgers e t al., 1990). The importance of proteolytic activity in the co-adherence of P. gingivalis and S. gordonii was demonstrated by Stinson et al (1992) Ray & Payne, 1988).…”
Section: Discussionmentioning
confidence: 99%